Strategy for Enhancing Organizational Commitment Through Authentic Leadership, Integrity, Teamwork, and Trust: An Empirical Study Using Path Analysis and SITOREM on Private High School Teachers in Depok, West Java - Masada Hirashita Tobing, Christine; Setyaningsih, Sri; Wulandari, Dian (International Journal Labs, 2026)
Commitment to the organization is a key factor in determining the success of an organization because it is directly related to loyalty, performance, and the sustainability of human power sources. However, in practice, there are still many organizations that face the problem of low employee commitment, which is marked by low loyalty, a lack of sense of responsibility, and an increasing desire to change jobs. This research aims to formulate improvement strategies for organizational commitment through strengthening leadership authenticity, integrity, teamwork, and trust. The research method used in this study is a quantitative method. Data collection in this study was done through a field survey. The data analysis method in this study uses path analysis and SITOREM analysis (Scientific Identification Theory to Conduct Research, Operation Research in Education Management). The research results show that leadership authenticity, integrity, and teamwork have a positive and significant influence on organizational commitment, both directly and indirectly through trust. Therefore, trust is proven to play a role as an effective mediator in strengthening the influence of leadership authenticity, integrity, and teamwork towards organizational commitment.